DEVELOPING CRITICAL READING SKILLS FOR INFORMATION AND ENJOYMENT - Didi Sudrajat (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2018)
Critical reading has been the issue in teaching reading throughout school programs.  The main objective of the critical reading is to achieve comprehension using various reading techniques.  Problems of reading comprehension, however, are difficult to handle and institutions require sets of teaching principles in a comprehensive plan.  The main problem of critical reading is asking students to involve in the reading manners that conform to the purposes of reading.  This paper presents a slight review of literature in teaching reading in general, providing theories on reading comprehension, reading process, and developing critical reading techniques.